2002
DOI: 10.1007/s101510200038
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial comparing LigaSure haemorrhoidectomy with the diathermy dissection operation

Abstract: The study was designed to compare LigaSure haemorrhoidectomy with open haemorrhoidectomy performed by means of diathermy excision. Fifty-sixty consecutive patients with third- and fourth-degree haemorrhoids were randomly allocated to undergo either LigaSure haemorrhoidectomy (29 patients) or diathermy haemorrhoidectomy (27 patients). All patients were evaluated for operative time, pain, post-operative analgesic requirements, time to first bowel movement, length of hospital stay, wound healing period, time to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 9 publications
11
100
3
1
Order By: Relevance
“…1,3,4,6,[8][9][10][11][12][13][14][15][16][17][18] Anal/rectal stenosis observed was about five times higher in EH group in spite of leaving islands of normal skin and mucosa to avoid stricture formation, which was managed conservatively. Recurrence, residual skin tags and prolapse were observed to be three times higher in SH group, comparable results were observed by Yang J et al [1][2][3][4][5] …”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,6,[8][9][10][11][12][13][14][15][16][17][18] Anal/rectal stenosis observed was about five times higher in EH group in spite of leaving islands of normal skin and mucosa to avoid stricture formation, which was managed conservatively. Recurrence, residual skin tags and prolapse were observed to be three times higher in SH group, comparable results were observed by Yang J et al [1][2][3][4][5] …”
Section: Discussionmentioning
confidence: 99%
“…Seven studies [22][23][24][25][26]29,30 reported data regarding pain on postoperative day 1, measured by the Visual Analogue Scale (VAS). A score of 0 represents no pain, while a score of 10 represents the worst pain.…”
Section: Meta-analysis Of Operative and Postoperative Parametersmentioning
confidence: 99%
“…24,28 All patients in both the LigaSure and conventional hemorrhoidectomy arms of the analysis had a mixture of internal and external hemorrhoidal components treated at the time of operation. The sensitivity analysis included 9 studies that scored 4 or more stars on the modified Jadad Scale, 22,24-28 5 studies that compared LigaSure with open hemorrhoidectomy, 22,[25][26][27]29 4 that compared LigaSure with closed hemorrhoidectomy, 23,24,28,30 7 that compared LigaSure with diathermy hemorrhoidectomy, [23][24][25][26][27]29,30 and 2 that compared LigaSure with scissors hemorrhoidectomy. 22,28 Results of operative and postoperative parameters and complications for LigaSure hemorrhoidectomy vs conventional hemorrhoidectomy groups are summarized in Table 2.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…However, we were not able to confirm these favorable results as reported in previous published studies [5,8,[15][16][17][18][19][20][21][22][23][24]. Most of these laparoscopic studies involved bowel surgery and compared LigaSure with ultrasonic devices [8,16,19,20].…”
Section: Discussionmentioning
confidence: 54%